2012
DOI: 10.1186/1751-0759-6-4
|View full text |Cite
|
Sign up to set email alerts
|

Somatic comorbidity in anorexia nervosa: First results of a 21-year follow-up study on female inpatients

Abstract: BackgroundAnorexia nervosa is a severe psychosomatic disease with somatic complications in the long-term course and a high mortality rate. Somatic comorbidities independent of anorexia nervosa have rarely been studied, but pose a challenge to clinical practitioners. We investigated somatic comorbidities in an inpatient cohort and compared somatically ill anorexic patients and patients without a somatic comorbidity. In order to evaluate the impact of somatic comorbidity for the long-term course of anorexia nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 13 publications
2
22
0
1
Order By: Relevance
“…This is consistent with the literature, given the severity of anorexia nervosa and the medical sequelae that accompany it [33,58]. The elevation for the patients with depression is also consistent with the physiological symptoms of major depression [59][60][61][62].…”
Section: Additional Findingssupporting
confidence: 89%
“…This is consistent with the literature, given the severity of anorexia nervosa and the medical sequelae that accompany it [33,58]. The elevation for the patients with depression is also consistent with the physiological symptoms of major depression [59][60][61][62].…”
Section: Additional Findingssupporting
confidence: 89%
“…In a 21-year follow-up study, Löwe et al (2001) showed that 16% of AN patients deceased due to consequences of their illness: about 50% died because of somatic complications leading to heart attack and the remainder committed suicide. Moreover, mortality is significantly more common among inpatients with somatic comorbidity (like renal, cardiac, bone, and digestive pathologies) than among inpatients without a somatic disease (Erdur et al, 2012). Finally, among the psychiatric comorbidities, AN is often associated with depression, anxiety, obsessive compulsive or personality disorders, and drug abuse (Erdur et al, 2012).…”
Section: Physiological Alterations In Anorexia Nervosamentioning
confidence: 99%
“…Among AN patients, 24.3% have a severe comorbid somatic disease [9], including electrolyte disorders, osteoporosis, renal insufficiency and cardiac dysfunction [10,11]. Most of them are reversible with improved nutritional status, but some of them can be life-threatening [12,13,14].…”
Section: Introductionmentioning
confidence: 99%